Personal Career Development With Appreciative Inquiry To Increase Employee Engagement - Arfian Hatta Istiqlal (Publikasi Indonesia, 2024)
This research aims to increase employee engagement by designing and implementing personal career development planning based on appreciative inquiry at PT. X. Then, personal career development planning activities based on appreciative inquiry gave rise to real action. The method in this research uses an appreciative inquiry approach, with a cycle of define, discovery, dream, design, and destiny with mini workshop media for employees representing each department when planning personal career development. The success of this research is measured by the process of the mini workshop and the outcomes of the intervention provided. The research results showed that the subjects gave an upbeat assessment of the mini-workshop activities and participated with spirit and enthusiasm. Then, the outcomes of this research show that the subjects experienced the impact of change, namely increased engagement from individuals and the implementation of actions that had been designed. In short, personal career development planning carried out by employees provides positive impacts and changes in organizational development